1995
DOI: 10.1128/jb.177.16.4792-4800.1995
|View full text |Cite
|
Sign up to set email alerts
|

Sterigmatocystin biosynthesis in Aspergillus nidulans requires a novel type I polyketide synthase

Abstract: A filamentous fungus, Aspergillus nidulans, produces the carcinogenic mycotoxin sterigmatocystin (ST), which is a polyketide-derived secondary metabolite. A gene (pksST) encoding the ST polyketide synthase (PKS st ) in A. nidulans was cloned, sequenced, and characterized. Large induced deletion mutants, which did not make ST or any ST intermediates, were used to identify genes associated with ST biosynthesis. Among the transcripts detected within the deletion region, which showed developmental expression with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 70 publications
3
110
0
Order By: Relevance
“…In addition to the biosynthetically related metabolites sterigmatocystin (8) (34) and dothistromin (9) (35), which clearly have a C 6 fatty acid starter unit, other PKS starter units are known. For example, in the synthesis of 1,3,6,8-tetrahydroxynaphthalene (10), where the starter unit is not obvious in the final product, malonyl-CoA has been demonstrated in vitro to be the starter unit as well as the extender unit (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the biosynthetically related metabolites sterigmatocystin (8) (34) and dothistromin (9) (35), which clearly have a C 6 fatty acid starter unit, other PKS starter units are known. For example, in the synthesis of 1,3,6,8-tetrahydroxynaphthalene (10), where the starter unit is not obvious in the final product, malonyl-CoA has been demonstrated in vitro to be the starter unit as well as the extender unit (36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the generation process of the lkc-PKS genes, the KS gene was fused with other genes in a unique order, while the AT and DH genes were not fused and remained as separate genes. The tandem alignment of two ACP domains was also found in the albicidin PKS [18] and several fungal type-I PKSs, for example, WA for naphtopyrone [19,20] and StcA for sterigmatocystin [21]. Huang et al [18] proposed that the second ACP domain in the albicidin PKS serves as a waiting position for growing chains to facilitate iterative condensation, although no experimental evidence was provided.…”
Section: Lkcf-lkcg Fusant Produced Lankacidin At a Similar Level To Tmentioning
confidence: 99%
“…Huang et al [18] proposed that the second ACP domain in the albicidin PKS serves as a waiting position for growing chains to facilitate iterative condensation, although no experimental evidence was provided. Fujii et al [21] disrupted each of the two tandem ACP domains in WA and showed that either ACP alone was enough for naphtopyrone synthesis. It is noteworthy that tandemly aligned doublet and triplet ACP domains were found even in the modular PKSs for mupirocin in Pseudomonas fluorescens [22].…”
Section: Lkcf-lkcg Fusant Produced Lankacidin At a Similar Level To Tmentioning
confidence: 99%
“…Recent evidence from the Steinbüchel laboratory has been interpreted to indicate that in vitro there are 25 polymer chains synthesized per molecule of C. Vinosum PHA synthase, which implies that there is a termination step (29). In animal fatty acid synthase and in some members of the polyketide synthase family, a thioesterase domain containing an essential serine is required for the hydrolysis step or lactone formation (30)(31)(32)(33). Thus, an alternative role for the conserved serine in PHA synthases might be controlling the chain length in a fashion that remains to be established.…”
mentioning
confidence: 99%